Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.13005/ojc/320409
|View full text |Cite
|
Sign up to set email alerts
|

Dereplication Study on Glaucium Aleppicum Boiss. in Jordan

Abstract: The secondary metabolite constituents of Glaucium aleppicum Boiss. et Hausskn. ex Boiass. (Papaveraceae) were investigated using an in-house developed Ultra Performance Liquid Chromatography-Photodiode Array-High Resolution Tandem Mass Spectrometry (UPLC-PDA-HRMS-MS/MS) method. In this study the powerful resolution and short analysis time afforded by UPLC coupled to the outstanding mass accuracy of an Orbitrap mass spectrometer was used to develop a rapid and effective dereplication method to identify secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Two peaks, 28 and 29, with precursor ions at m / z 354.1237 and 370.1624, respectively, had the same basic skeleton of protopine alkaloid. By comparing their fragmentation behavior with those reported by Barakat, et al [ 57 ], compound 28 was unambiguously identified as protopine, while compound 29 as α-allocryptopine, identified for the first time in G. acutidentatum . Diagnostic ions with m / z values of 189 and 188, resulting from B-ring cleavage and/or RDA fragmentation, observed in the MS/MS spectra of both compounds, confirmed our assumption [ 50 ].…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Two peaks, 28 and 29, with precursor ions at m / z 354.1237 and 370.1624, respectively, had the same basic skeleton of protopine alkaloid. By comparing their fragmentation behavior with those reported by Barakat, et al [ 57 ], compound 28 was unambiguously identified as protopine, while compound 29 as α-allocryptopine, identified for the first time in G. acutidentatum . Diagnostic ions with m / z values of 189 and 188, resulting from B-ring cleavage and/or RDA fragmentation, observed in the MS/MS spectra of both compounds, confirmed our assumption [ 50 ].…”
Section: Resultsmentioning
confidence: 61%
“…Compound 26 presented a similar fragmentation pattern but differed in the intensity of the generated product ions. A comparison of the product ions with the highest intensity at m/z 311.1266 for compound 23 and at m/z 279.0994 for compound 26 allowed their identification as isocorydine and corydine, respectively, reported in G. aleppicum by Barakat et al (2016). Two compounds, 27 and 31, afforded precursor ions at m/z 372 and a molecular formula of C21H25NO5, suggesting the glaucine structure with an additional OH group.…”
Section: Chemical Profile Of Extractsmentioning
confidence: 94%